ANALISIS FAKTOR-FAKTOR PEMBENTUK CAMELS PA DA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sri Hermuningsih (Jurnal Manajemen Indonesia, 2015)
The aims of this study is to determine the major factors that form the performance of the Banking CAMELS listed in Indonesia Stock Exchange. The population in this study are all banking companies listed on the Stock Exchange in 2011-2012.The sampling method used in this study was purposive sampling method with the criteria is listed for 2 years. Samples were worth using as much as 72 recordable banking. The method of analysis using factor analysis with SPSS. The results showed that the 26 variables used as a proxy variable rate shaper CAMELS, 26 comunalities pass the test but there are two ratios that do not enter the group most variables, is debt management and CAR.